Tools of the trade. - Brown, Andrew (New Statesman, 1999)
The science fiction writer Neal Stephenson compares a computer operating system to a builder's drill. In an essay on his website, he maintains that, like the Hole Hawg drill, anything less powerful than the Unix system can only be considered a toy. He argues that Microsoft's attempt to make all the operating systems that its application software runs on may be a futile exercise. Stephenson's essay can be located at < http://www.cryptonomicon.com/beginning.html >.